PREFERENSI KONSUMEN TERHADAP ORGANOLEPTIK COOKIES NON TERIGU (CONSUMER PREFERENCE TO COOKIES GLUTEN FREE’S ORGANOLEPTIC) - Cita Eri Ayuningtyas (Persagi, 2019)
Cookies is a popular snack in the world made from wheat flour. Level of wheat flour consumption in Indonesian in 2015 was 1,552 per capita.In other side, cookies gluten free as well as water yam flour, maizena flour, bekatul, mocaf, suweg, and rice flour is developing to replace wheat flour despite of less popular. The research was aim to identificate consumer preference of cookies gluten free’s organoleptic. Research design used complete randomized design (RAL)which the varians of rice flour, tapioca flour, and maizena flour. Organoleptic test used to identificate level of consumer preference. Result of the research showed that level of consumer preference to the varians of rice flour, tapioca flour, and maizena flour has no significantly different (p=0,008). 10 from 27 consumer prefered cookies 412 which all the atribut texture, colour, and flavour. Conclusion : Cookies 412 was the best cookies than others followed by its texture atribut.